Antimalarial herbal remedies of Bukavu and Uvira areas in DR Congo: An ethnobotanical survey. (1st March 2020) - Manya, Mboni Henry; Keymeulen, Flore; Ngezahayo, Jérémie; Bakari, Amuri Salvius; Kalonda, Mutombo Emery; Kahumba, Byanga Joh; Duez, Pierre; Stévigny, Caroline; Lumbu, Simbi Jean-Baptiste
Abstract: Ethnopharmacological relevance: The main objective of the present study was to collect and gather information on herbal remedies traditionally used for the treatment of malaria in Bukavu and Uvira, two towns of the South Kivu province in DRC. Material and methods: Direct interview with field enquiries allowed collecting ethnobotanical data; for each plant, a specimen was harvested in the presence of the interviewed traditional healers (THs). The recorded information included vernacular names, morphological parts of plants, methods of preparation and administration of remedies, dosage and treatment duration. Plants were identified with the help of botanists in the herbaria of INERA/KIPOPO (DRC) and the Botanic Garden of Meise (Belgium), where voucher specimens have been deposited. The results were analysed and discussed in the context of previous published data. Results: Interviewees cited 45 plant species belonging to 41 genera and 21 families used for the treatment of malaria. These plants are used in the preparation of 52 recipes, including 25 multi-herbal recipes and 27 mono-herbal recipes. Apart of Artemisia annua L. (Asteraceae; % Citation frequency = 34%) and Carica papaya L. (Caricaceae; % Citation frequency = 34%), the study has highlighted that the most represented families are Asteraceae with 12 species (26%), followed by Fabaceae with 7 species (16%) and Rubiaceae with 4 species (9%). For a majority of plants, herbal medicines are prepared from the leaves in the form of decoction and administered by oral route. Conclusion: Literature data indicate that part of cited species are already known (38%) and/or studied (30%) for antimalarial properties, which gives credit to the experience of Bukavu and Uvira interviewees and some level of confidence on collected information. The highly cited plants should be investigated in details for the isolation and identification of active ingredients, a contribution to the discovery of new possibly effective antimalarials. Graphical abstract: Image 1